Dirofilaria immitis Microfilariae and Third-Stage Larvae Induce Canine NETosis Resulting in Different Types of Neutrophil Extracellular Traps - Muñoz-Caro, Tamara; Conejeros, Iván; Zhou, Ershun; Pikhovych, Anton; Gärtner, Ulrich; Hermosilla, Carlos; Kulke, Daniel; Taubert, Anja (Frontiers in Immunology, 2018)
Heartworm disease is a zoonotic vector-borne disease caused by Dirofilaria immitis mainly affecting canids. Infectious third-stage larvae (L3) are transmitted to the definitive hosts via culicid mosquitos; adult nematodes reside in the pulmonary arteries and in the right heart releasing unsheathed first stage larvae (microfilariae) into the bloodstream leading to chronic and sometimes fatal disease. So far, early innate immune reactions triggered by these different D. immitis stages in the canine host have scarcely been investigated. Therefore, D. immitis microfilariae and L3 were analysed for their capacity to induce neutrophil extracellular traps (NETs) in canine polymorphonuclear neutrophils (PMN). Overall, scanning electron microscopy (SEM) analysis revealed both larval stages as strong inducers of canine NETosis. Co-localization of PMN-derived extracellular DNA with granulocytic histones, neutrophil elastase or myeloperoxidase in parasite-entrapping structures confirmed the classical characteristics of NETosis. Quantitative analyses showed that both larval stages triggered canine NETs in a time-dependent but dose-independent manner. Moreover, parasite-induced NET formation was not influenced by the parasites viability since heat-inactivated microfilariae and L3 also induced NETs. In addition, parasite/PMN confrontation promoted significant entrapment but not killing of microfilariae and L3. Both, NETosis and larval entrapment was significantly reversed via DNAse I treatments whilst treatments with the NADPH oxidase inhibitor DPI failed to significantly influence these reactions. Interestingly, different types of NETs were induced by microfilariae and L3 since microfilarial stages merely induced spread and diffuse NETs whilst the larger L3 additionally triggered aggregated NET formation.